Innovative and creative schools and mathematical education: A possible way for school inclusion - Rosa, Erica Aparecida Capasio [UNESP]; Baraldi, Ivete Maria [UNESP] (FapUNIFESP (SciELO), 2021)
The present work offers a presentation of possible ways for school inclusion through the analysis of narratives of educational subjects, that belong to innovative and creative schools. The narratives were produced using Oral History as a methodology. We present some considerations on school management, curriculum, community involvement with networks, school environment, and teaching methodology and, specifically, on the mathematics teaching methodology of the schools covered. Finally, we conclude that the practices and actions of the investigated schools are a capacity to effect school inclusion, although at different times it is still necessary to pay more attention, for example, to the school environment and the teaching methodology, mainly for mathematics teaching. However, they are a source of inspiration for other school units to promote the inclusion of their students with disabilities.
Escolas Inovadoras e Criativas e a Educação Matemática: Caminhos possíveis para a inclusão escolar
Keywords: Inclusive Mathematical Education; Mathematics teaching; Narratives; Oral history; Students with disabilities